Coping Strategy for Primipara Mother That Experinced In Postpartum Depression - Nasekah, Faridhatun (EMPATHY Jurnal Fakultas Psikologi, 2013)
Abstrak This study aims to determine the presenting symptoms in primipara mother who experience postpartum depression, postpartum depression trigger, coping strategies used in primipara mother who experience postpartum depression as well as the positive and negative effects of postpartum depression is. Research methods that researchers use qualitative research method is the type of phenomenology. Subjects were two respondents who experienced postpartum depression. Data collection techniques in this study was conducted using semi-structured interviews. Leveraging the use of sources of data and methods of triangulation. Results showed symptoms in the mother can be seen from primipara psychological and physical symptoms, such as sensitivity, sadness, confusion, dizziness, crying easily, less angry for no reason, erratic mood swings, feelings of guilt and worthlessness excessive, search greater attention than ever before, the emergence of excessive jealousy against children, the emergence of doubt in the care of children, loss of appetite and severe weight loss, fatigue and insomnia. Stressors trigger postpartum depression in subjects including; presence of decreased attention and support is given from a large family, unpreparedness through pregnancy, physical environment residence YS subject, the subject is doing a dual role CC and applied parenting parents subject CC. Coping strategies used by both subjects is problem focused coping and emotional focused coping, including; planful problem solving, confronative coping, seeking social support, information seeking, distancing, escape avoidance, accepting responsibility, and self-criticism. Positive and negative impacts that arise are subject YS can find the meaning of life and the love of children and her husband, on the of subject CC can provide information to the family about the support needed primipara mother. The subject makes a negative impact YS become more sensitive, prone to crying, and the emergence of feelings of regret, where as subject CC lost interest in to the move. The conclusion suggests that the subject YS more often use problem focused coping strategies than emotional focused coping so subject YS correct the problem so it is not getting worse. As for the of subject CC subject tend to use the emotional focused coping with the problems that focused the subject naturally does not immediately improved. Keyword : Postpartum Depression, Coping Strategy.